2016
DOI: 10.1002/navi.134
|View full text |Cite
|
Sign up to set email alerts
|

3D Multi-Copter Navigation and Mapping Using GPS, Inertial, and LiDAR

Abstract: As the use of unmanned aerial vehicles has become more prevalent, the need for a reliable threedimensional positioning and navigation capability is required to enable operation in challenging environments where the Global Positioning System (GPS) may not be available. For many of these environments, there may not be one particular method to solve the positioning navigation problem. Therefore, we have selected a set of dissimilar sensor technologies and implemented an integrated navigation method that can suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…Light Detection and Ranging (LiDAR) is becoming a promising technology for obstacle warning and avoidance in a variety of manned and unmanned aircraft applications. LiDAR's outstanding angular resolution and accuracy characteristics are coupled to its good detection performance in a wide range of incidence angles and weather conditions, providing an ideal obstacle avoidance solution, which is especially attractive in sUAS [30]. The Laser Obstacle Avoidance Marconi (LOAM) system is one such system, which was jointly developed and tested by SELEX-ES and the Italian Air Force Research and Flight Test Centre.…”
Section: ) Active Systemsmentioning
confidence: 99%
“…Light Detection and Ranging (LiDAR) is becoming a promising technology for obstacle warning and avoidance in a variety of manned and unmanned aircraft applications. LiDAR's outstanding angular resolution and accuracy characteristics are coupled to its good detection performance in a wide range of incidence angles and weather conditions, providing an ideal obstacle avoidance solution, which is especially attractive in sUAS [30]. The Laser Obstacle Avoidance Marconi (LOAM) system is one such system, which was jointly developed and tested by SELEX-ES and the Italian Air Force Research and Flight Test Centre.…”
Section: ) Active Systemsmentioning
confidence: 99%
“…The geo-references laser and camera data can then be used in the detect and avoid function. This concept bases, in part, on work performed by the authors [17] [18].…”
Section: Conceptional Approach For Multi-mode Navigation Inflightmentioning
confidence: 99%
“…As shown in Figure 6, laser range scanners, vision systems as well as a laser or radar altimeter are good candidates for integration with GNSS in addition to an inertial measurement unit, to provide continuity of the navigation function in areas where the GNSS-only solution is not sufficient. These integration strategies have been explained in detail in previous work by the authors [17][18] [20]. Some preliminary outputs are shown in Fig.…”
Section: Multi-mode Navigationmentioning
confidence: 99%
“…Environment observing sensors such as the LiDAR sensor have been used to generate odometry measurements by measuring changes in the observed environment. Dill et al have shown that integrating LiDAR with INS is able to obtain global anchor navigation solutions to meter‐accuracy when GPS is available . Soloviev has demonstrated that 2D line LIDAR scan matching can be paired with GPS for navigating in environments where GPS navigation alone can be difficult .…”
Section: Related Workmentioning
confidence: 99%